2010
DOI: 10.1007/s11695-010-0215-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Improvement in Depressive Symptoms Following Bariatric Surgery

Abstract: High rates of depression are continually reported in obesity, as is a remarkable decrease in depressive symptoms following weight loss. Negative attitudes towards one's self appears to be driving elevated BDI scores rather than the overlap in physical symptoms between obesity and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 50 publications
(95 reference statements)
2
33
1
1
Order By: Relevance
“…Hayden et al 14 observed that weight loss greatly reduces depressive symptoms in bariatric patients regardless of their preoperative condition. This same position is advocated by more recent studies that consider that preoperative psychological assessments should identify and propose treatment of pathological situations, rather than excluding the patient from surgery [15][16][17][18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…Hayden et al 14 observed that weight loss greatly reduces depressive symptoms in bariatric patients regardless of their preoperative condition. This same position is advocated by more recent studies that consider that preoperative psychological assessments should identify and propose treatment of pathological situations, rather than excluding the patient from surgery [15][16][17][18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…These authors have observed that 23% of patients had an increase in their antidepressant use, 40% continued to require the same dose of antidepressant, 18% had a change in antidepressant medication and only 16% of patients had a decrease or discontinued the antidepressant therapy 62 . In addition, in a sample of 67 bariatric patients with high level of depressive symptomology was found that 30% used antidepressants preoperatively and 24% were on antidepressants after bariatric surgery 55 .…”
Section: Mood Disordersmentioning
confidence: 99%
“…The majority of studies have reported a decrease in depression and depressive symptoms after bariatric surgery 24,27,[48][49][50][51][52][53][54][55][56] . Women seem to show a more marked decline than men 57 .…”
Section: Mood Disordersmentioning
confidence: 99%
“…The need to accommodate the growing numbers of severely obese patients will require wideranging changes in new and existing healthcare facilities. Of concern, WLS patients have a higher prevalence of mental health disorders and substance abuse problems [5].…”
Section: Betsy Lehman Center For Patient Safety and Medical Error Redmentioning
confidence: 99%